2023
DOI: 10.1038/s41392-023-01439-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting protein modifications in metabolic diseases: molecular mechanisms and targeted therapies

Abstract: The ever-increasing prevalence of noncommunicable diseases (NCDs) represents a major public health burden worldwide. The most common form of NCD is metabolic diseases, which affect people of all ages and usually manifest their pathobiology through life-threatening cardiovascular complications. A comprehensive understanding of the pathobiology of metabolic diseases will generate novel targets for improved therapies across the common metabolic spectrum. Protein posttranslational modification (PTM) is an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 593 publications
0
26
0
1
Order By: Relevance
“…Many studies have confirmed DNA methylation changed in liver biopsy of patients with NAFLD 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] (Figure 3). A recent investigation revealed a marked reduction in global DNA methylation among 47 individuals diagnosed with NAFLD compared to a cohort of 18 lean subjects without NAFLD, as assessed via liver biopsy.…”
Section: Clinical Researchmentioning
confidence: 86%
“…Many studies have confirmed DNA methylation changed in liver biopsy of patients with NAFLD 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] (Figure 3). A recent investigation revealed a marked reduction in global DNA methylation among 47 individuals diagnosed with NAFLD compared to a cohort of 18 lean subjects without NAFLD, as assessed via liver biopsy.…”
Section: Clinical Researchmentioning
confidence: 86%
“…Moreover, several drug candidates for T2DM have been proved to regulate protein PTMs. For example, Glucokinase activators (GKAs), including dorzagliatin, MK-0941 and AZD1656, also promotes SUMOylation of pancreatic glucokinase, (Wu et al, 2023), implying PTM can be the potential drug targets for T2DM. Thus, further in-depth studies of PTMs in insulin secretion are in need.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-induced histone PTMs have profound consequences in the pathology of diabetic complications [ 40 ]. Decreased expression of glucose transporter GLUT4, encoded by Slc2a4 gene, in the skeletal muscle of T1D- and T2D-like animals has been detected [ 32 ].…”
Section: Ptms In Type 1 Diabetesmentioning
confidence: 99%